Usefulness of contrast-enhanced ultrasound (CEUS) in Inflammatory Bowel Disease (IBD). Issue 8 (August 2018) - Pecere, Silvia; Holleran, Grainne; Ainora, Maria Elena; Garcovich, Matteo; Scaldaferri, Franco; Gasbarrini, Antonio; Zocco, Maria Assunta
Abstract: Intestinal ultrasonography has emerged as a cheap, non-invasive and readily accessible modality for the assessment of a number of gastroenterological diseases. Over the last decade, particularly due to the widespread use of biological agents in Inflammatory Bowel Disease (IBD), guidelines regarding management and follow-up advise more regular disease assessment and surveillance in order to guide treatment adjustments, and provide more personalised care. Given the young age of the majority of patients with IBD the availability of an alternative modality to harmful radiation or the risks of endoscopy for this indication offers an appealing advantage. Intestinal ultrasonography has been shown to be as sensitive and specific for detecting IBD as both computed tomography and magnetic resonance enterography, and endoscopic evaluation. More recent developments in the technology of ultrasonography equipment and the use of intravenous contrast agents (contrast enhanced ultrasonography, known as CEUS), have significantly increased the ability to both detect disease location, determine the disease activity and also potentially the difference between fibrotic and inflammatory segments. This review focusses specifically on the value of CEUS for the diagnosis of both Crohn's disease and Ulcerative Colitis, in determining disease activity, extraintestinal complications, determination of fibrosis as well as its more recent use in assessing and predicting response to biological and immunosuppressive therapies.